Comparison of the cadmium and lead contents of oysters (Crassostrea iredalei) harvested from Altavas, Aklan and Dumangas, Iloilo. - Torreno, Erwin Pabuaya (2016.)
Oysters are nutritious and popular seafood delicacy grown in the waters of Panay Island. However, due to the quality of their growing waters and their feeding habits, they have become a major food safety concern. Oysters absorb and accumulate heavy metals such as cadmium and lead, which can cause illness when ingested. This study was conducted to measure the amount of cadmium and lead in oysters (Crassostrea iredalei) grown in Altavas, Aklan and Dumangas, Iloilo. The oysters were also characterized in terms of moisture content, protein content, and fat content. The oysters from Altavas contained an average of 1.95 mg kg-1 Pb. Meanwhile, the oysters from Dumangas contained an average of 1.95 mg kg-1 Cd and 3.80 mg kg-1 Pb. The oysters sampled were safe for human consumption in terms of Cd 3.80 mg kg-1 Pb. The oysters sampled were safe for human consumption in terms of Cd and Pb concentrations based on the maximum permissible levels established by the Philippines and Hong Kong. However, they exceeded the maximum permissible levels of Singapore, Malaysia, Australia, New Zealand, United States, and the European Union. There were no significant differences (p>0.05 by t-test) in the Cd and Pb concentrations of oysters grown in both locations. In terms of nutritional contents, oysters from Altavas had 84.41% moisture (WB), 34.02% protein (DB), and 1.402% fat (DB), while oysters from Dumangas contained 87.99% moisture (WB), 41.81% protein (DB), and 1.862% fat (DB). Two-sample t-tests at the 95% confidence level showed that the % moisture content of oysters from Dumangas was higher than those from Altavas. However, there were no significant differences (p>0.05 by t-test) in the protein and fat contents of oysters grown in both locations.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Oysters; Crassostrea iredalei